2021
DOI: 10.3390/ijerph18147378
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Associated Factors among Frontline Healthcare Workers in the COVID-19 Epicenter of Da Nang City, Vietnam

Abstract: Frontline healthcare workers (HCWs) involved in the COVID-19 response have a higher risk of experiencing psychosocial distress amidst the pandemic. Between July and September 2020, a second wave of the COVID-19 pandemic appeared in Vietnam with Da Nang city being the epicenter. During the outbreak, HCWs were quarantined within the health facilities in a bid to limit the spread of COVID-19 to their respective communities. Using the stress component of the 21-item Depression, Anxiety and Stress Scale (DASS-21), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
1
15
1
1
Order By: Relevance
“…Until now, research has failed to comprehensively investigate the child-care work environment during the pandemic, but focused instead on the stress levels of parents and caregivers in need of child care during COVID-19 [39][40][41][42]. Moreover, recent pandemicrelated stress and mental health research was predominately concerned with health care workers resulting in ample literature [43][44][45][46][47][48][49][50][51][52]. While surveys endeavored to holistically explore ECPs' work practices and well-being during the pandemic, they lacked scientific rigor [53,54].…”
Section: Introduction 1background and Current Researchmentioning
confidence: 99%
“…Until now, research has failed to comprehensively investigate the child-care work environment during the pandemic, but focused instead on the stress levels of parents and caregivers in need of child care during COVID-19 [39][40][41][42]. Moreover, recent pandemicrelated stress and mental health research was predominately concerned with health care workers resulting in ample literature [43][44][45][46][47][48][49][50][51][52]. While surveys endeavored to holistically explore ECPs' work practices and well-being during the pandemic, they lacked scientific rigor [53,54].…”
Section: Introduction 1background and Current Researchmentioning
confidence: 99%
“…Health care workers identified the importance of PPE being suitable and well stocked, having regular training and receiving consistent guidelines, issues also raised by other HCWs (Ananda-Rajah et al, 2021; Nguyen et al, 2021; Vindrola-Padros et al, 2020). Some thought the guidelines were not sufficiently strict or timely as early in the pandemic masks were not comprehensively or effectively used.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to physical health impacts, the COVID-19 pandemic also has a huge impact on the mental health of medical staff, causing depression, anxiety, and insomnia [ 7 ]. A study in Da Nang city, during the second wave of the pandemic, showed an increase in the prevalence of stress among frontline HCWs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%